Ana Gabriela Macedo, Joana Passos, Elena Brugioni (orgs.) Prémios literários: o poder das narrativas, as narrativas do poder. porto: afrontamento, 2016. 212 pp. - Pereira, Margarida Esteves (Diacrítica, 2018)